Degradation of lignocellulosic substrates by Pleurotus ostreatus and Lentinus squarrosulus - Fasiku, Samuel Adedayo; Wakil, Sherifah Monilola; Alao, Olaoluwa Kehinde (The Asia Journal of Applied Microbiology, 2023)
Lignocellulosic substrates are wastes in the environment whose reducing sugars are not readily available for use. Biological pretreatment is the use of microorganisms and/or their metabolites to break down substrates to obtain simple sugars which is also cheap compared with other pretreatment techniques. This work is aimed at degrading lignocellulosic substrates with higher mushrooms to obtain simple sugars that could be used as raw materials for other industrial processes. The two mushrooms [Pleurotus ostreatus (PO) and Lentinus squarrosulus (LS)] with the ability to produce cellulase, xylanase, and lignase were used for degradation of lignocellulosic substrates [groundnut shell (GS), maize cob (MC), maize straw (MS), rice straw (RS) and sugarcane bagasse (SB)]. The residual extractives, cellulose, hemicellulose, lignin, and reducing sugar contents were determined every 7 days. Least extractives (1.12 %), hemicellulose (15.09 %), lignin (17.60 %), and cellulose (5.60 %) were recorded in PO-degraded MS, POLS-degraded GS, LS-degraded GS, and PO-degraded MS at 28, 35, 49 and 42 days of degradation, respectively. The highest reducing sugar contents (mg/g) obtained in GS (11.83), MS (27.03), SB (28.70), and RS (37.96) were recorded when degraded by PO for 49, 14, 7, and 49 days, respectively while that of MC (13.32) was recorded when degraded by LS for 42 days. Reducing sugar obtained was higher from sole degradation with PO compared with LS and POLS. Degraded MS, RS, and SB had better yield of reducing sugar than GS and MC. The amount of reducing sugar released varied with substrates, organisms, and degradation time.